Auxiliar de atividades educativas na educação infantil: constituição histórica e tensões de uma ocupação no âmbito da rede municipal de educação de Goiânia - Edir, Eliane Garcia de Brito (2014)
This study was part of the research line Education, Labour and Social Movements from Graduate School of Education Program at Federal University of Goiás. We had as main goal to study the genesis and development historical movement of the Assistant Educational Activities‘s job, whose workers act alongside teachers in service to children in Municipal child Education Centers and municipal schools that have pre-school classes from Goiânia‘s Department of Education. We start from the understanding that knowing the structure and evolution of the post of an Assistant Educational Activities in Goiânia‘s Municipal Education is an aspect of fundamental importance for the understanding of the early childhood education reality which today legally makes up the first step of Basic Education in Brazilian educational system. This research work is guided by a socio-historical vision of man and society. To achieve the objectives this study proposes, we opted for developing a predominantly qualitative research. For the analyzes development, we initially seek to conduct a comprehensive literature review on the work, the women work, the teaching work, the childhood and their education. We also developed a documentary analysis considering the contents of the Federal Constitution (FC, 1988), the Statute of Children and Adolescents (1990), the Law of Directives and Bases of National Education (1996), National Curriculum guidelines for early childhood education (2009). At the municipal level, we analyzed City Board of Education Resolutions, Goiânia‘s Early Childhood Education Regiments as well as other data and documents that we collected at the Department of Education. The next step was the interviews‘ proposition with the intention of recognizing the historical context of the Assistant Educational Activities‘ job in Goiânia. With this task, we seek to identify the actors involved and learn about the circumstances and the elements of the need to found the position of Assistant Educational Activities in order to compose a chart that would illustrate the post of Assistant Educational Activities‘ creation process and that would allow us to reflect about the implications of that job‘s creation for early childhood education in Goiânia. The study indicated that the proposition of the post of Assistant Educational Activities occurred in the course of transition of responsibility from childhood education to the Municipal Department of Education and it was based on a triple topic: the immediate need of hiring staff, the job‘s transience intention and the impending rise in staff training to work in early childhood education. This survey revealed, however, dissension of these topics, since the need of hiring staff was not surpassed; there has been a throwback in demanding training of these professionals and, in spite of this transience, the regulation and the effectiveness of the post of Assistant Educational Activities point, instead, to its consolidation definitively.